A Noise Adaptive Approach to Impulse Noise Detection and Reduction - Irum, Isma; Sharif, Muhammad; Yasmin, Mussarat; Raza, Mudassar; Azam, Faisal (Nepal Journal of Science and Technology, 2015)
A noise adaptive filter has been proposed in this study aiming to estimate the original image pixel values in the presence of impulse noise in monochromatic images. The proposed filter approach is noise adaptive that as the percentage of noise density increases in the image, the size of neighborhood in filtering window is also increased. Proposed approach comprises of two stages, one is impulse noise detection and the other is impulse noise reduction or cancellation. First stage is based on median and mean distance and thresholding whereas the second stage is based on reconstruction of the image using the values of neighboring pixels of the pixel under consideration detected as contaminated pixel by first stage. Reconstruction is done by estimating reference values using uncorrupted pixels in the neighborhood of pixel under consideration. The proposed method has been compared to various existing methods by using peak signal to noise ratio (PSNR) for measuring the objective quality strength. To measure the impulse noise detection the method has also been compared with other existing methods using the ratio of mis etection (MD) and false detection (FD). DOI: http://dx.doi.org/10.3126/njst.v15i1.12016 Nepal Journal of Science and Technology Vol. 15, No.1 (2014) 67-76